2014
DOI: 10.1016/j.cognition.2013.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Where is the chocolate? Rapid spatial orienting toward stimuli associated with primary rewards

Abstract: a b s t r a c tSome stimuli can orient attentional resources and access awareness even if they appear outside the focus of voluntary attention. Stimuli with low-level perceptual salience and stimuli with an emotional content can modulate attention independently of voluntary processes. In Experiment 1, we used a spatial cuing task to investigate whether stimuli that are controlled for their perceptual salience can modulate the rapid orienting of attention based exclusively on their affective relevance. Affectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
108
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 90 publications
(114 citation statements)
references
References 48 publications
4
108
2
Order By: Relevance
“…Analogous Pavlovian conditioning. The procedure that we previously elaborated (Pool et al, 2014) was applied here. Briefly, three initially neutral images were attributed the Pavlovian roles of "baseline," "CSϩ," and "CSϪ."…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Analogous Pavlovian conditioning. The procedure that we previously elaborated (Pool et al, 2014) was applied here. Briefly, three initially neutral images were attributed the Pavlovian roles of "baseline," "CSϩ," and "CSϪ."…”
Section: Methodsmentioning
confidence: 99%
“…The Pavlovian stimuli consisted of three geometric complex figures typically used in human conditioning paradigms (Gottfried, O'Doherty, & Dolan, 2003;O'Doherty et al, 2004;Valentin, Dickinson, & O'Doherty, 2007) that in a pilot study (n ϭ 26) were rated as similarly neutral on a pleasantness scale (see Pool et al, 2014). They were displayed in the center of the computer screen with a visual angle of 8°.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Like exogenous attention, emotional attention is rapid and involuntary; it is also comparable to endogenous attention, however, as it strongly depends on some of the observer's internal factors, such as the affective state (e.g., a state of anxiety; Bar-Haim et al, 2007). Some investigators have proposed that exogenous attention, endogenous attention, and emotional attention have an additive influence on attentional selection (Brosch et al, 2011), thereby suggesting that these three systems can operate simultaneously and that they each have a unique influence on attention (Pourtois et al, 2013). Moreover, emotional attention has been shown to be particularly mediated by a neuronal structure (i.e., the amygdala) that differs from the structures that mediate exogenous and endogenous attention (Vuilleumier, 2005;Vuilleumier & Brosch, 2009).…”
mentioning
confidence: 99%
“…These two subcomponents of attentional biases are dissociable processes that can be differentially manipulated (Born, Kerzel, & Theeuwes, 2011). Recent studies (Pool, Brosch, Delplanque, & Sander, 2014;Theeuwes & Belopolsky, 2012) parsing the contribution of these two subcomponents in attentional bias for positive stimuli suggested that the bias is driven by an initial orienting more than a difficulty in disengaging attention. In the present meta-analysis, a moderator was coded on the subcomponent of attentional bias (initial orienting or difficulty in disengagement) when the experimental paradigm used in the study allowed such a distinction.…”
mentioning
confidence: 99%